SASTRA LISAN SEBAGAI REFLEKSI KEARIFAN LOKAL DALAM MENJAGA SIKAP, PERILAKU, DAN ETIKA - Winarti Winarti; Siti Hardiyanti Amri (STABN Raden Wijaya Wonogiri, 2020)
Local wisdom has a close relationship with society and culture. Culture is an abstract knowledge that exists in a nation. Through culture, individuals as part of an ethnic group will manifest behaviors patterns to interact with their social environment. In this case, oral literature plays an important role in constructing local wisdom as a part of culture of which function to maintain attitudes, behaviors, and ethics found in social life. All elements involved in local wisdom synergize in upholding norms, values, culture, attitudes, behaviors, and ethics as reflected in the tradition of tabu, myth and folklore, traditional expressions, and traditional ceremonies.